Efisiensi Konsentrasi dan Suhu Larutan HCl pada Proses Hot Dip Galvanizing - Agussari, Cici ; Ella; Iskandar, Taufik; Abrina Anggraini, Sinar Perbawani (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2019)
Hot Dip Galvanize is a type of iron coating process with other metals, such as zinc, bydipping into a tub of liquid zinc. The Hot Dip Galvanize process consists of severalstages, namely degreasing, pickling, fluxing, dipping, and quenching. Liquid zinc entersand attaches to the iron surface by a diffusion mechanism. Hot Dip Galvanize is widelyused as a method of protecting iron against corrosion.Some ways that can slow the rate of corrosion reactions include coating the metalsurface so that it is separated from the corrosive media, making the metal alloy so thatit is corrosion resistant, and by adding certain substances that function as corrosionreaction inhibitors